Analyzing Values In Bimanese Proverb - I, Ismiati; Aristia, Erni Sona; Bulandari, Putri; S, Sumarlin (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study faims to analyse the kinds of moral values and function of the Bima proverbs. It was descriptive qualitative research. The research subjects were Bima Minority in Taliwang District of West Sumbawa Regency. The data was collected through observation, literary study/documentation and in-depth interview, then analyzed through reduction, presentation, interpretation, conclucion. This study found three kinds of moral values in Bima proverbs. Those were attitude, manner and obligation. Through the value of attitude, Bima society are taught to do valuable things for themselves and others. In the value of manner, the society is advised to act in good ways. The value of obligation describes the responsibility of Bima society as individual and social human being. Further finding of this study describes that Bima Provers function for giving advaice, forming behavior, and as rhetorical device. Giving advice means that through proverbs, the society are directed to do valuable things for their life, others, and for the environment in which they are interacted. Patterns of behaviour describes the message that people need to build the social controls. Functioning as rhetorical device, proverbs teach people to be able to adapt in a new natural interaction.